2016
DOI: 10.1158/0008-5472.can-15-3190
|View full text |Cite
|
Sign up to set email alerts
|

Exome-Scale Discovery of Hotspot Mutation Regions in Human Cancer Using 3D Protein Structure

Abstract: The impact of somatic missense mutation on cancer etiology and progression is often difficult to interpret. One common approach for assessing the contribution of missense mutations in carcinogenesis is to identify genes mutated with statistically nonrandom frequencies. Even given the large number of sequenced cancer samples currently available, this approach remains underpowered to detect drivers, particularly in less studied cancer types. Alternative statistical and bioinformatic approaches are needed. One ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 68 publications
0
129
0
Order By: Relevance
“…However, the methods differ in detail, e.g., in the tumor sets analyzed, the definition of 3D clusters, and the statistical test applied, and so they produce different lists of candidate functional mutations. For example, Mutation3D identified 399 mutated residues in 75 genes as likely functional [17], HotMAPS identified 398 mutated residues in 91 genes [18], and Hotspot3D identified 14,929 mutated residues in 2466 genes [19], whereas our method identified 3404 mutated residues in 503 genes (Additional file 6: Table S5 and Additional file 7: Figure S2). Somewhat surprisingly, only 15 mutated residues were identified by all four methods, all of which were also previously identified as single-residue hotspots [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the methods differ in detail, e.g., in the tumor sets analyzed, the definition of 3D clusters, and the statistical test applied, and so they produce different lists of candidate functional mutations. For example, Mutation3D identified 399 mutated residues in 75 genes as likely functional [17], HotMAPS identified 398 mutated residues in 91 genes [18], and Hotspot3D identified 14,929 mutated residues in 2466 genes [19], whereas our method identified 3404 mutated residues in 503 genes (Additional file 6: Table S5 and Additional file 7: Figure S2). Somewhat surprisingly, only 15 mutated residues were identified by all four methods, all of which were also previously identified as single-residue hotspots [6].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the mutational 3D clusters identified by three alternative methods (Mutation3D [17], HotMAPS [18], and Hotspot3D [19]) and our method are largely complementary (Additional file 7: Figure S2). While different mutational and structural datasets used by these four tools may have led to some of the differences observed, methodological differences likely dominate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hotspots of somatic events of individual patient data can be compared to cancer genome databases [88]. Mutation pattern in combination with three-dimensional protein structures reveals the mutation distribution of specific functional regions and can highlight hotspots or oncogenic drivers [8992]. The study on efficient detection of genomic drivers in malignant melanoma identified co-occurrence of a mutational and copy number hotspot on chromosome 7 including the known BRAF locus [13].…”
Section: Precision Medicine Profile Of Malignant Melanoma Patient Witmentioning
confidence: 99%
“…The Mutations tab allows the user to toggle through submitted mutations alongside statistically significant 3D mutation clusters from TCGA data; statistically significant mutation clusters are precomputed for each of 31 TCGA cancer subtypes using the HotMAPS algorithm. 13 In Figure 1C, MuPIT is located at the Annotations tab, and user-submitted mutations (shown in green) are spatially proximal to known TGFBR1 binding and active sites (cyan and blue), suggesting a potential mechanistic role for these mutations.…”
Section: Cravat 4xmentioning
confidence: 99%